How to Interpret Liver Function Test in Daily Practice - Yudith Setiati Ermaya; Dwi Prasetyo (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: The liver is a multi-function organ that plays a role in producing various important secrete, synthesis and metabolic functions. The term liver function test is also used to refer to the hepatocyte synthesis function, such as serum albumin and prothrombin time. In this paper, we will discuss how to interpret various liver function test results in daily practice as well as approach to abnormal liver function tests. Discussion: Abnormal result of liver function test is frequently found in asymptomatic healthy patients who are undergoing routine screening. On the contrary, some patients with liver disease may appear with normal liver function test. As such, there are some limitations regarding this particular test. ALT (SGPT) is the primary marker of hepatocellular injury due to it being more sensitive and specific than AST (SGOT). Conjugated bilirubin level of more than 20% of total bilirubin level is a strong indication of hepato-biliary disease and is always pathogenic. GGT is only increased in cholestatic conditions and not in bone disease. As such, GGT levels can help to distinguish abnormalities in the liver or bones in conditions of increased ALP levels in the blood. Conclusion: Serum liver biochemistry examination is very useful and effective in assessing liver function. Understanding the proper interpretation of liver enzymes will help clinicians easier to diagnose or predict a disease as well as condition related to the liver in daily practice.